2020
DOI: 10.1038/s41598-020-69517-7
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular gp96 is a crucial mediator for driving immune hyperactivation and liver damage

Abstract: Liver failure leads to the massive necrosis of hepatocytes, releasing large amounts of intracellular components including damage-associated molecular patterns (DAMPs). We found that extracellular gp96 levels in serum were elevated in patients with chronic hepatitis B infection (CHB) and acuteon-chronic liver failure (ACLF). Meanwhile, the gp96 level positively correlated with hepatic necroinflammation. We employed two mouse liver damage and liver failure models induced by lipopolysaccharide (LPS) plus d-galact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
(55 reference statements)
1
9
0
Order By: Relevance
“…Single-cell RNA sequencing of blood antigen-presenting cells in severe COVID-19 reveals that pathways related to NF-κB signaling were upregulated in plasmacytoid dendritic cells and CD14 + monocytes ( 29 ). We and others also show that extracellular gp96 induced proinflammatory cytokines (e.g., IL-6 and TNF-α) in activated immune cells ( 30 32 ). Taken together, our study indicates that extracellular gp96 is released from the damaged and necrotic cells after SARS-CoV-2 infection and stimulates monocytes and other proinflammatory immune cells to secrete IL-6 through the NF-KB pathway.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Single-cell RNA sequencing of blood antigen-presenting cells in severe COVID-19 reveals that pathways related to NF-κB signaling were upregulated in plasmacytoid dendritic cells and CD14 + monocytes ( 29 ). We and others also show that extracellular gp96 induced proinflammatory cytokines (e.g., IL-6 and TNF-α) in activated immune cells ( 30 32 ). Taken together, our study indicates that extracellular gp96 is released from the damaged and necrotic cells after SARS-CoV-2 infection and stimulates monocytes and other proinflammatory immune cells to secrete IL-6 through the NF-KB pathway.…”
Section: Discussionsupporting
confidence: 68%
“…SARS-CoV-2 infection may lead to an uncontrollable immune response and subsequent sepsis or septic shock through the release of various DAMPs and cytokines ( 33 , 34 ). A number of studies have demonstrated the ability of extracellular gp96 as a DAMP to drive inflammation ( 30 , 31 ). Our study found that levels of plasma gp96 and IL-6 were closely correlated in COVID-19 patients that and gp96 can act as DAMP to activate CD14 + cells to secrete IL-6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar findings have been reported in the context of acute deterioration of liver function in patients with chronic hepatitis B infection 77 . Intracellular components released by necrotic hepatocytes (such as HMGB1, cyclophilin A, gp60) contribute to exacerbating hepatic inflammation in experimental models of liver failure 78,79 . The clinical and experimental evidence supporting the contribution of liver-derived DAMPs to systemic inflammation in alcohol-induced ACLF is weaker than that for the driving-role of gut-derived PAMPs.…”
Section: [H1] Systemic Inflammation In Cirrhosismentioning
confidence: 99%